1975
DOI: 10.2307/1589189
|View full text |Cite
|
Sign up to set email alerts
|

Hemagglutinating Properties of CELO, an Oncogenic Avian Adenovirus

Abstract: Chicken-embryo-lethal-orphan (CELO) virus, Phelps strain, agglutinated erythrocytes at 37 C. The hemagglutinating activity, which is a function of complete and incomplete virus particles, was sensitive to heat but not to pH. The soluble components of the virus were similar in sedimentation characteristics to those obtained from human adenovirus type 1. The effects of chemical and physical agents on CELO hemagglutinin, CELO infectivity, and red-cell receptors suggested that the last were protein in nature and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1977
1977
1984
1984

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Norrby (1971) noted fibres of 14 nm on FAV-1 virus, similar to members of Rosen's subgroup 2 which FAV-1 resembles in its haemagglutination properties. El Mishad et al (1975), however, demonstrated fibres measuring 17.5 nm on FAV-1 particles. Potter etal.…”
Section: Properties Of Fowl Adenovirusesmentioning
confidence: 89%
See 1 more Smart Citation
“…Norrby (1971) noted fibres of 14 nm on FAV-1 virus, similar to members of Rosen's subgroup 2 which FAV-1 resembles in its haemagglutination properties. El Mishad et al (1975), however, demonstrated fibres measuring 17.5 nm on FAV-1 particles. Potter etal.…”
Section: Properties Of Fowl Adenovirusesmentioning
confidence: 89%
“…Later El Mishad et al (1975) demonstrated that FAV-1 (Phelps) failed to agglutinate dog, guinea-pig, hamster, human, mouse, rabbit and rhesus monkey erythrocytes. Rat cells were agglutinated and haemagglutination took place at 4°C and 37°C.…”
Section: Haemagglu Tinationmentioning
confidence: 99%
“…Avian Adenoviruses. El Mishad et al (1975) demonstrated that while rat erythrocytes were agglutinated at 4°C and 37°C, maximum titers were achieved between pH 6 and pH 9, with tempera tures between 20°C and 45°C. Anderson et al (1971) demonstrated that peaks of hemagglutinating activity were recorded at densities of 1.32 and 1.34 gm/ml in association with bands of complete and incomplete particles.…”
Section: Viral Dnamentioning
confidence: 98%
“…The mouse 1 (AL) strain has a fiber length of 29 nm (Wigand et al, 1977). However, Norrby (1971) found that the fiber length of Fl was 14 nm, and El Mishad et al (1975) demonstrated fibers of 17.5 nm on Fl particles. However, Norrby (1971) found that the fiber length of Fl was 14 nm, and El Mishad et al (1975) demonstrated fibers of 17.5 nm on Fl particles.…”
Section: A Morphologymentioning
confidence: 99%
See 1 more Smart Citation